Evaluasi atas SP2DK pada Pengusaha Kena Pajak - Muslimin; Sonya Azharani Nugrahani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In Indonesia, the tax system in place is a self-assessment system, through which taxpayers independently fulfill their tax obligations. Despite this, in practice, taxpayers often encounter non-compliance or errors in reporting. Consequently, the SP2DK is utilized by the DJP to ensure the effective operation of the self-assessment system and the accurate fulfillment of taxpayers' obligations. This article aims to evaluate the implementation of SP2DK for the 2022 Tax Year from the perspective of PKPs who receive SP2DK. The primary focus of this research is to understand how a taxable enterprise encounters and responds to SP2DK and to ascertain the steps taken in providing information to the DJP. The methodology employed involves qualitative research using a case study approach, with the research subjects being Individual Taxpayers who are taxable enterprises and own businesses in the food, beverage, and tobacco wholesale trade and who receive SP2DK in the city of XYZ. The results of this research reveal an underpayment of VAT amounting to IDR 114,191,457 and income tax amounting to IDR 182,504,137, which is repaid in installments within 6 months from the date of the LHP2DK.